The inferior temporal cortex is a potential cortical precursor of orthographic processing in untrained monkeys - Rishi Rajalingham (Nature Portfolio, 2020)
The neuronal mechanisms underlying recognition of written letters remain unknown. Here, the authors show that populations of neurons in the ventral visual pathway of macaque monkeys encode orthographic stimuli, indicating that this pathway might be a precursor of orthographic processing abilities.